In vitro, efek antidiabetes dan antikolestrol kopasanda (Chromolaena odorata L.) - Rahmawati, Rahmawati; Baits, Muzakkir; Putri, Hemalia; Nurhikmah, Nurhikmah (Faculty of Pharmacy, Universitas Muslim Indonesia, 2025)
The leaves of the kopasanda plant (Chromolaena odorata L.) contain alkaloids, flavonoids, saponins, terpenoids and tannins which have the potential to be anti-diabetic and anti-cholesterol. In vitro research has been carried out on the ethanol extract of kopasanda leaves (Chromolaena odorata L.) to determine the potential of α-glucosidase enzyme inhibitor compounds as antidiabetic by determining the IC50 value and the potential to reduce cholesterol levels as an anticholesterol by determining the EC50 value. Testing for the inhibitory activity of the α-glucosidase enzyme used the spectrophotometer method with a microplate reader at a wavelength of 405 nm, with acarbose as a comparison. The results showed that the activity of the ethanol extract of kopasanda leaves (Chromolaena odorata L.) as an inhibitor of the α-glucosidase enzyme obtained an IC50 value of 444.019 µg/mL in the very weak category. In testing the anti-cholesterol potential using a UV-Vis spectrophotometer with measurements at a wavelength of 672 nm, the calculation results obtained an EC50 value of 1,017.118 µg/L. This shows that the activity of the ethanol extract of kopasanda leaves (Chromolaena odorata L.) has the potential to inhibit cholesterol.